Highly efficient conservative treatment of pectus carinatum in compliant patients - Loff, Steffan (European journal of pediatric surgery, 2015)
Purpose: Pectus carinatum is a thoracic deformity, which causes severe psychological problems for affected patients but almost no physical limitations. Invasive procedures are difficult to justify for this reason. We present a conservative therapy which leads to complete resolution in most cases when performed properly. Methods: Between January 2008 and December 2012, 69 patients from 4 to 17 years with pectus carinatum were treated with a custom-fitted brace. Patients were stratified in children, adolescents, and adults.Results: Mean therapy time was 7 months. Mean time of daily brace wearing was 12 to 15 hours. The results were evaluated by pictures taken before and after the therapy and from a patient interview. Standardized lateral views revealed a mean correction angle of 10 degrees in the children's group and 5 degrees in the adolescent group. In the adolescent group, 82% of patients judged the result as “excellent” or “good.” In this large group with 56 patients, those who reported the result “unchanged” had a mean daily brace wearing time of 8.73 hours, those who judged the result as “good” 14.53 hours, and those who judged the result as “excellent” 18.36 hours. Conclusion: Our results show that pectus carinatum is efficiently treated with a customized brace therapy within 7 to 12 months. Best correction can be achieved in children and young adolescents. Daily brace-wearing time should be above 14 hours, ideally 24 hours. Duration of the treatment should be around 1 year. Treatment results correlate directly with the cooperation of the patients.
Gesehen am 20.12.2018
Published online August 11, 2014